Forging the Bond with Gen Z: The Roles of Brand Experience and Cultural Equity for Indonesian Local Fashion Brands - Laila Mara Nasution; Reizano Amri Rasyid; Azmil Chusnaini; Mohamad Yusak Anshori; Candraningrat (Jurnal Manajemen dan Organisasi, 2026)
This study investigates the mediating role of cultural equity in the relationship between brand experience and brand attachment, framing cultural equity as a psychological mechanism through which brand experiences are translated into enduring emotional bonds. Using a quantitative design, data were collected from consumers of Indonesian local fashion brands and analyzed through partial least squares structural equation modeling to evaluate the proposed relationships among constructs. The results show that brand experience contributes positively to the development of cultural equity and directly strengthens brand attachment. In addition, cultural equity plays a significant role in reinforcing brand attachment, indicating that culturally meaningful brand associations are central to the formation of emotional ties. The findings further demonstrate that cultural equity partially mediates the link between brand experience and brand attachment, suggesting that experiences shape attachment not only through direct affective responses but also through cultural meaning creation. Practically, these results highlight the importance for brand managers to design experiences that extend beyond functional and emotional value by embedding culturally relevant narratives and symbolism across consumer touchpoints. The study advances consumer–brand relationship literature by providing evidence that cultural equity is a critical pathway through which brand experiences evolve into deep and sustainable brand attachment.